1996
DOI: 10.1002/(sici)1097-010x(19960101)274:1<15::aid-jez2>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Hypoosmotic stimulation of ornithine decarboxylase activity in the brine shrimpArtemia franciscana

Abstract: In the brine shrimp, long‐term (several days) osmotic and ionic regulation is controlled principally by the activity of Na+K+ATPase. However, short‐term cell volume regulation in Artemia and most euryhaline crustaceans is not understood. In this study, Artemia stage 1 nauplii reared at 32 ppt salinity and exposed to hypoosmotic conditions (12 or 4 ppt) exhibited an immediate increase in the activity of ornithine decarboxylase, the rate‐limiting enzyme in polyamine synthesis. ODC activity increased within 15 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recent studies have found that the gill tissues showed obvious inflammatory reactions under alkalinity stress in crustaceans, resulting in tissue damage, but enzyme activity experiments reveal that the activity of NKA, CA and NKCC are increased [ 59 61 ], which can cope with the shock of alkalinity stress. In this study, we got similar results as above, which provided support for our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the gill tissues showed obvious inflammatory reactions under alkalinity stress in crustaceans, resulting in tissue damage, but enzyme activity experiments reveal that the activity of NKA, CA and NKCC are increased [ 59 61 ], which can cope with the shock of alkalinity stress. In this study, we got similar results as above, which provided support for our experiment.…”
Section: Discussionmentioning
confidence: 99%